Reflecting on Diversity through a Simulated Practicum Classroom: A Case of International Students - Finn, Mark; Phillipson, Sivanes; Goff, Wendy (Journal of International Students, 2020)
This study aimed to investigate how international students draw on their own cultural identity to reflect on their teaching practice in a simulated classroom in the Australian context. Each simulated teaching session that the students participated in was recorded and sent to the pre-service teachers for later review and reflection. The pre-service teachers were required to produce a 1000 word written reflection of their teaching practice with an explicit focus on how they supported culture, difference and diversity of need in their lesson. Using the Rodger’s framework, these reflections were analyzed using the Leximancer software, a lexical semantic tool, to identify the shared and unique experiences that pre-service teachers from the diverse backgrounds face in refining and developing their teaching practice.